2017
DOI: 10.1002/jmv.24987
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus infection and associated risk factors among pregnant women attending antenatal care in health facilities of Tigray, Northern Ethiopia

Abstract: Hepatitis B virus infection is one of the leading causes of liver disease in the world. This study was conducted to determine the prevalence of HBV infection and associated risk factors among pregnant women in Northern Ethiopia using a cross-sectional study design. A total of 328 pregnant women were included in this study. Clinical and socio-demographic data of the pregnant women were collected using a structured questionnaire by nurses or midwives during their ANC visit. For the detection of HBsAg, 5 mL of ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
23
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 25 publications
(32 reference statements)
13
23
5
Order By: Relevance
“…Pregnant women with multiple sexual partners had 3 times (AOR3.2; 95% CI: 1.3-7.6%) more likely to develop HBV infection than their counterparts. This nding is similar to other studies [17,24,[40][41][42][43]. Blood transfusion has been recognized as a major risk factor for transmission of HBV throughout the world.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Pregnant women with multiple sexual partners had 3 times (AOR3.2; 95% CI: 1.3-7.6%) more likely to develop HBV infection than their counterparts. This nding is similar to other studies [17,24,[40][41][42][43]. Blood transfusion has been recognized as a major risk factor for transmission of HBV throughout the world.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, study participants with a family history of HBV infection (AOR 3.5,95% CI:1.7-3.7) had more likely to be infected with HBV than compared to their counterparts. This is similar to the study done in Tigray, Ethiopia [43]. In contrast, this is inconsistent with other studies [24,40].…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…For example, a retrospective study in Cameroon found a significant relationship between occupation [10] and age [6,11], and HBV infection among pregnant women [11]. In Nigeria, Anaedobe, Fowotade [12], revealed that pregnant women with multiple sexual partners [6,10,[13][14][15] and those who experienced early sexual debut were more likely to be infected with HBV. Other risk factors include marital status, history of abortion, blood transfusion and surgery, family history of HBV infection, and alcohol intake [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…All the included studies were cross-sectional study designs and the most recent was conducted in 2019. Regarding regional coverage of HBV prevalence studies, more than half of the studies were obtained from Amhara region [80] 2016 Somali Blood donor Entire sampling Abera B., et al [79] 2017 Amhara HIV positive children Random sampling Abera B., et al [78] 2014 Amhara Apparently healthy Random sampling Akalu GT., et al [77] 2016 SAC Healthcare workers Convenient sampling Amsalu A., et al [76] 2018 2018 Amhara Blood donors Consecutive sampling Birku T., et al [67] 2015 Amhara Military personnel Random sampling Bisetegen FS., et al [66] 2016 SNNPR Blood donors Consecutive sampling Chernet A., et al [65] 2017 SNNPR Pregnant women Entire sampling Dabsu R., et al [64] 2014 Oromia Pregnant women Convenient sampling Demsiss W., et al [63] 2018 Amhara Students Random sampling Deressa T., et al [20] 2017 Amhara HIV positive Random sampling Deressa T., et al [62] 2018 Amhara Blood donors Entire sampling Desalegn Z., et al [84] 2013 SAC Healthcare workers Convenient sampling Desalegn Z., et al [83] 2016 Oromia Pregnant women Entire sampling Erena AN., et al [61] 2014 Oromia General population Random sampling G/micheal A., et al [60] 2013 Oromia Healthcare workers Random sampling G/egziabher D., et al [59] 2016 SAC General population Entire sampling G/mariam AA., et al [58] 2019 Amhara Healthcare professional Entire sampling Habte Y., et al [57] 2016 SAC Blood donors Entire sampling Hebo HJ., et al [56] 2019 Oromia Healthcare workers Random sampling Heyredin I., et al [55] 2019 Mixed Blood donors Consecutive sampling Kabato AA., et al [86] 2016 SNNPR Blood donors Entire sampling Kebede W., et al [85] 2017 Oromia Prisoners Random sampling Mekonnen A., et al [54] 2015 SAC Waste handlers Random sampling Mekonnen D., et al [53] 2014 Amhara Diabetes mellitus * Metaferia Y., et al [52] 2016 SNNPR Pregnant women Convenient sampling Mezgebo TA., et al [81] 2018 Tigray Pregnant women * Mohammed Y., et al [51] 20...…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%